The History of Earth and Life: Escape Room for High School Students - Alicia Giner-Baixauli; Hugo Corbí; Olga Mayoral (Education Sciences)
Introduction: This study investigates how different teaching strategies influence students’ learning outcomes and engagement. Objective: The primary aim is to evaluate the knowledge and motivation of students in the first year of high school (17 years old), before and after participating in an escape room activity on the History of the Earth and Life. Methodology: The research involved 50 students, divided into a control group that received traditional lectures and an experimental group that participated in a gamified experience. Pre- and post-intervention assessments were conducted to measure knowledge acquisition, and motivation was assessed through a survey. Statistical analyses, including ANOVA, were performed to compare the effectiveness of both teaching methods. Results: The study shows significant statistical differences between the two strategies, demonstrating a notable increase in learning through gamification (F(1, 48) = 21; p < 0.001). Additionally, students in the experimental group perceived the methodology as more engaging, highlighting its dynamic, interactive, and motivating nature. Conclusions: The findings suggest that incorporating interactive and dynamic learning experiences can foster deeper engagement with the content.